Challenges to ACP trade with Europe after the Uruguay Round - Koning, Antonique (European Centre for Development Policy Management MaastrichtNL, 1994)
Sets out the background for the current trade performance of ACP countries. Considers the likely impact of the Uruguay Round on ACP preferences and exports. Presents several practical steps to ensure that existing preferences are better utilised. Outlines some options that can guide the ACP response to the challenges of a new trade environment - in the mid-term and beyond.